Cellulose nanofibers, nanocrystals, and bacterial nanocellulose: Fabrication, characterization, and their most recent applications - Hadis Rostamabadi; Yograj Bist; Yogesh Kumar; Meral Yildirim‐Yalcin; Tugce Ceyhan; Seid Reza Falsafi (Future Postharvest and Food)
Abstract In nature, cellulose is present in fibrillar structures with alternative crystalline and amorphous fragments. The application of various chemical treatments (acid hydrolysis, enzymolysis, and oxidation) could lead to the extraction and purification of crystalline compartments in the form of cellulose nanocrystals. On the other hand, applying harsh mechanical treatments (milling, ultrasonication, high‐pressure processing, grinding, microfluidization, etc.) could result in the degradation of cellulose macrostructures into nano‐fibrillated segments without depletion of the amorphous fractions. These structures are called cellulose nanofibers. Bacterial nanocelluloses (BNCs) are another nanostructure of cellulose that is generated through the bottom–up technique. BNCs are the purest forms of cellulose nanostructures (CNSs). Hitherto, various spectroscopy and microscopy characterization techniques have been developed for in‐depth investigation of CNSs. The valuable information obtained via such instrumental techniques has opened windows on new horizons for the application of CNSs in novel realms. Nowadays, CNSs have found a seat in biomedical, packaging, emulsification, water filtration, and textile applications. In this review, after describing various forms of CNSs and their fabrication methods, the most recent techniques that have been utilized for the characterization of these structures plus their current application in different realms are comprehensively overviewed.